Experiencing Relative Deprivation as True Crime: Applying Cultural Criminology to the Qanon Superconspiracy Theory - Caputo-Levine, Deirdre (2022)
This essay builds upon earlier studies of the QAnon superconspiracy theory by applying cultural criminology as a framework to investigate the significance of QAnon and the events that facilitated the rise of the superconspiracy and the associated political movement. QAnon has had multiple impacts that should be of interest to criminologists. In the United States, QAnon was involved with the 2020 election, as adherents believed messages posted by "Q" referred to President Trump as a messiah and Trump tacitly acknowledged the group. In addition, QAnon has international influence, most recently in the "trucker" convoy in Canada and anti-vaccine protests in New Zealand and Germany. This essay utilizes cultural criminology to introduce the framework of relative deprivation theory and emphasize the importance of the gaze from above and below in structuring relative deprivation. In addition, we discuss the role of cultural understandings of victimization in shaping ideology and physical frameworks used by QAnon